Ibn Khaldun's theory of 'Asabiyyah and 'Umran' : the case of declining political power of the United Malays National Organization (UMNO) - Syed Hamid Syed Jaafar Albar (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research examines the decline and erosion of UMNO as a dominant political party of Malaysia through the perspective of Ibn Khaldun's theory of 'asabiyyah and 'umran. It uses the qualitative method of data collection from Ibn Khaldun's original works. After discussing Ibn Khaldun's theory of 'asabiyyah and 'umran, UMNO's 'umranic contributions and erosion of Malay 'asabiyyah are discussed in detail. The study outlines how 'asabiyyah led to UMNO's rise to prominence, gain of political power, bringing of progress and development of Malaysia to an 'umranic stage before it started to decline and erode in accordance with the five stages of Ibn Khaldun's theory of rise and fall of civilizations. The study finds that the early leaders of UMNO played a significant role in fostering group feeling and solidarity of the Malays ('asabiyyah). 'Asabiyyah was the engine that propelled UMNO to acquire mulk and transform the Malays and Malaysia into an 'umranic society. The study also concludes that the later leaders of UMNO contributed to the weakening of the Malay 'asabiyyah and the fall of UMNO from power in the 14th General Elections in 2018. The process of UMNO's decline and erosion of political power is primarily caused by the leaders' failures and shortcomings. The study, among others, recommends that for UMNO to be relevant again in the current political landscape, it must initiate new and serious approaches and initiatives to change itself and must focus on good governance and rule of law in a multi-ethnic Malaysian society.